Diabetic Patients’ Perception of Diabetic Foot Ulcers: A Qualitative Study - Leila Mardanian Dehkordi; Raheleh Javanbakhtian (Journal of Qualitative Research in Health Sciences)
Background: Diabetic foot ulcer (DFU) is one of the serious and debilitating challenges faced by patients with diabetes, which imposes a financial burden on both patients and healthcare systems. Although this problem can be prevented and treated by proper foot care techniques, many patients do not follow the recommendations. Accordingly, this study aimed to rely on deep insight and knowledge to explain diabetic patients’ perception of DFU and identify appropriate care and support practices to prevent and manage it.Methods: This descriptive study was conducted using qualitative content analysis. The participants were 15 patients with diabetes, who visited the healthcare centers in Shahrekord, Iran selected using purposive sampling. Data were collected through face-to-face and semi-structured interviews with the participants until data saturation. Data were analyzed simultaneously with data collection using the method proposed by Graneheim and Lundman.Results: Data analysis led to the identification of four main categories including being destined to a doomed fate, self-treatment, indifference to obsessive care, and care-inhibiting beliefs.Conclusion: To gain a deeper understanding of standard foot care, the causes of foot ulcers, preventive care services, and existing treatments, different strategies can be adopted such as peer education or using the experiences of other patients with ulcers.